Neuroprotective Effect of Demethylsuberosin, a Proteasome Activator, against MPP+-induced Cell Death in Human Neuroblastoma SH-SY5Y Cells - Kim, Bo-Hyung; Kwon, Jaeyoung; Lee, Dongho; Mar, Woongchon (Planta Medica Letters, 2015)
Demethylsuberosin isolated from the roots of Cudrania tricuspidata demonstrated a potent proteasome activator by enhancing all three chymotrypsin-like, trypsin-like, and caspase-like proteasome activities in a 20S proteasome activity assay. It also attenuated the 1-methyl-4-phenylpyridinium-induced dysfunction of the chymotrypsin-like and caspase-like activities of proteasome in SH-SY5Y cells with EC50 values of 0.76 µM and 0.82 µM, respectively. Additionally, demethylsuberosin protected neuronal cells against 1-methyl-4-phenylpyridinium-induced cell death with an EC50 value of 0.17 µM, while the EC50 value of betulinic acid was 4.29 µM. We are reporting that demethylsuberosin is a potent proteasome activator with a neuroprotective effect, suggesting a possible candidate for the protection or treatment of neurodegenerative diseases such as Parkinsonʼs disease.
Keywords: Cudrania tricuspidata; Moraceae; demethylsuberosin; neuroprotection; proteasome activator; 1-methyl-4-phenylpyridinium (MPP+)